Working ourselves to happiness: finding meaning at work through coaching in South Africa - Bailes, Silvia Ana (My University, 2014)
Happiness and meaning in individual and organisational functioning is addressed, as well as the role of executive and business coaching in supporting this process. Theories of applied positive psychology, as the conceptual framework underpinning happiness, and philosophies of meaning, are defined and tested within a South African context of trauma and violence. Happiness, the science, is controversial, but is explored as scientific research reports positive affects that could be relevant in alleviating related SA-specific conditions of stress and dysfunction. The study is qualitative, with data collected via semi-structured one-on-one interviews. An inductive approach is applied to the interpretation of data to arrive at recurring themes. Happiness is found to be both a concept and an outcome. The outcome is shown to comprise personal needs, intrinsic motivations and balance, the sum of which represents a construct of well-being, that leads to personal growth and performance. Limitations of the intrinsic motivations on personal growth are discussed, and the meaning motivation shown to be ‘unlimited’ and sustainable. Combining the intrinsic motivations with positive behaviours, with meaning, as a central theme, is demonstrated to result in sustainable positive impacts for individuals and their organisations. Happiness and meaning, namely, well-being, are found to be important elements of individual and organisational functioning and effectiveness. Differences in frames of reference relative to happiness are relevant in the South African context and socio-economic environment. Individuals overlook potential opportunities of benefit to organisations by ignoring the socio-economic environment when restricting the influence of their roles to their internal environments. Organisations can help employees to find meaning in their work that leads to workplace happiness and work satisfaction. Organisational threats to well-being are evidenced in negative affects that impact performance and pose a potential governance risk. Reciprocal benefits to employees and employers are evident when employees are supported by effective embedded organisational well-being programmes that mitigate this risk. Threats to employees in the well-being areas of being treated as human beings, purpose, learning, and balance, are evident. This includes existential angst and loss of hope which is attributed to SA-specific socioeconomic problems of significant proportion. In combination with trauma and violence that is endemic to SA society, this results in negative affects that impact on well-being and performance. These are important areas that could benefit from coaching support. Organisations can implement coaching processes to support employees find meaning in their personal and work lives that are of benefit to organisations. Differing perceptions of coaching needs between individuals and organisations are evident. Organisations do not appear to be aware of employees’ need for coaching in the area of purpose and meaning. Specialists express discomfort when dealing with organisations on soft issues of this nature, indicative of mindsets in need of change if coaching is to be given the organisational emphasis it deserves in supporting sustainable well-being. Findings are synthesised into a conceptual model of meaning for sustainable individual and organisational well-being, with specific reference to the coaching process. The conceptual model outlines the component parts of well-being and their symbiotic and systemic relationships for supporting personal meaning at work.
Thesis (M.M. (Business Executive Coaching))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: Employees; Training; Coaching; Job satisfaction; South Africa